Intravenous administration of synthetic platelets (SynthoPlate) in a mouse liver injury model of uncontrolled hemorrhage improves hemostasis. Issue 6 (June 2018) - Dyer, Mitchell R.; Hickman, DaShawn; Luc, Norman; Haldeman, Shannon; Loughran, Patricia; Pawlowski, Christa; Sen Gupta, Anirban; Neal, Matthew D.
Abstract : BACKGROUND: Clinical resuscitative treatment of traumatic hemorrhage involves transfusion of RBC, platelets and plasma in controlled ratios. However, use of such blood components, especially platelets, present many challenges including availability, portability, contamination risks, and short shelf-life, which limit the use of platelet transfusions outside of large trauma centers such as remote civilian hospitals and austere prehospital settings. This has prompted significant research in platelet substitutes that may resolve the above issues while providing platelet-mimetic hemostatic action. In this framework, we have developed a synthetic platelet surrogate, SynthoPlate, by integrative decoration of platelet function mimetic peptides on a biocompatible lipid nanovesicle platform. We have previously demonstrated hemostatic capability of SynthoPlate in correcting tail-bleeding time in thrombocytopenic mice. Building on this, we hypothesized that SynthoPlate transfusion would decrease bleeding in a murine model of acute hemorrhagic shock. METHODS: A validated model of uncontrolled intraperitoneal hemorrhage, via liver laceration was used to induce hemorrhagic shock in mice. SynthoPlate, control (unmodified) particles, and normal saline were administered as pretreatment and recue infusions to mice undergoing liver laceration and evaluated for hemostatic benefit by determining differences in blood loss and monitoring real-time hemodynamic data. RESULTS: Pretreatment SynthoPlate transfusion resulted in significant reduction of blood loss following hemorrhage, compared with control particles or normal saline treatment (0.86 ± 0.16 g control particles [CP] vs. 0.84 ± 0.13 g normal saline [NS] vs. 0.68 ± 0.09 g SynthoPlate, p < 0.005). SynthoPlate transfused mice demonstrated improved hemodynamics taking significantly longer to develop post-injury hypotension (168.3 ± 106.6 seconds CP vs. 137 ± 58 seconds NS vs. 546.7 ± 329.8 seconds SynthoPlate, p < 0.05). SynthoPlate infusion following liver laceration, that is, rescue transfusion, also resulted in a significant decrease in blood loss (0.89 ± 0.17 g CP vs. 0.92 ± 0.19 g NS vs. 0.69 ± 0.18 g SynthoPlate, p < 0.05). CONCLUSION: Transfusion of SynthoPlate particles reduces blood loss in a murine model of liver injury, and SynthoPlates may represent a viable transfusion product for the mitigation of blood loss in acute, severe hemorrhagic shock.